2001
DOI: 10.4067/s0718-19572001000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de Tetraselmis chuii, Nannochloris oculata y Dunaliella salina sobre el crecimiento poblacional de Apocyclops distans (Copepoda,Cyclopoidae) en diferentes condiciones de temperatura e iluminación

Abstract: Efecto de Tetraselmis chuii, Nannochloris oculata y Dunaliella salina sobre el crecimiento poblacional de Apocyclops distans (Copepoda,Cyclopoidae) en diferentes condiciones de temperatura e iluminación Effect of Tetraselmis chuii, Nannochloris oculata and Dunaliella salina on the population growth of Apocyclops distans (Copepoda, Cyclopoidae) at different temperature and ligth conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…These findings were similar with previous researchers. The densities for A. distans (Hsu 1999; Velasquez et al 2001), Acartia tsuensis (Ohno and Okamura 1988), Acartia sp. (Schipp et al 1999), A. royi (Cheng et al 2001), and Paracyclopina nana (Lee et al 2006) were 6.5, 2.0, 7.0, 33, and 96–119 ind./mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were similar with previous researchers. The densities for A. distans (Hsu 1999; Velasquez et al 2001), Acartia tsuensis (Ohno and Okamura 1988), Acartia sp. (Schipp et al 1999), A. royi (Cheng et al 2001), and Paracyclopina nana (Lee et al 2006) were 6.5, 2.0, 7.0, 33, and 96–119 ind./mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(Schipp et al 1999), A. royi (Cheng et al 2001), and Paracyclopina nana (Lee et al 2006) were 6.5, 2.0, 7.0, 33, and 96–119 ind./mL, respectively. Velasquez et al (2001) reported that better growth performance of A. distans was due to highest volume and motility of T. chuii compared to N. oculata and Dunaliella salina . The better growth and density of A. dengizicus fed on T and CT may be related to feeding behavior of this species, which preferred T due to its motility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, C. calcitrans and T. tetrathele were used for culture of A. dengizicus during their life history (including nauplii, copepodids and adults) (Farhadian 2006; Farhadian, Yusoff & Arshad 2008) as optimum diets. Better growth and development of A. dengizicus were due to the high volume and motility of T. tetrathele (Velasquez, Rosas, Carbrera, Millan & Hernandez 2001), feeding behaviour of this species, which preferred T. tetrathele due to its motility (Farhadian 2006), and biosynthesis of DHA from linolenic acid, 18:3n‐3 (Lee, Park, Lee & Kang 2006). The DHA:EPA:ARA ratios of T. tetrathele and C. calcitrans were 4.2:8.4:5.1 and 4.4:11.2:5.1 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…mL −1 receiving C. calcitrans, T. tetrathele and their combination respectively (Table 4). The densities for A. distans (Hsu 1999; Velasquez et al 2001); Acartia tsuensis (Ohno & Okamura 1988); and Acartia sp. (Schipp, Bosamans & Marshall 1999) were 6.5, 2.0 and 7.0 ind.…”
Section: Discussionmentioning
confidence: 99%
“…Before stocking, the seeds were first acclimated to the desired salinity by decreasing or increasing one unit per hour, and then to temperature, by placing the nauplii in 1L flask one hour prior to stocking in each tank with the corresponding temperature. Each experimental unit was stocked with one ind mL −1 for a total of 400 individuals per bottle based on the recommendations of Velásquez et al (2001).…”
Section: Copepod Stockingmentioning
confidence: 99%